Early Warning System for Disaster Preparedness in Local Flood Management: A Literature Review - Tedjaprasadja, Leonardo (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: Flooding remains one of the most recurrent and devastating natural hazards, disproportionately impacting low-lying and poorly drained areas, particularly in developing countries. Exacerbated by rapid urbanization, climate change, and inadequate infrastructure, flood-related disasters increasingly affect socioeconomically vulnerable populations. Despite the predictable nature of such events, local-level disaster preparedness remains insufficient, largely due to the absence or inefficiency of Early Warning Systems (EWS). Methods: This paper investigates the role of EWS in strengthening community-based flood preparedness by applying the United Nations Office for Disaster Risk Reduction (UNDRR) four-component framework: risk knowledge, monitoring and warning service, dissemination and communication, and response capability. Using a qualitative, framework-based methodology, the study assesses each component through case study analysis, technological review, and institutional mapping. Result and Discussions: Findings indicate that while EWS provides a robust conceptual tool for flood risk mitigation, their implementation is frequently hindered by technical, institutional, social, and financial barriers. These include unreliable monitoring infrastructure, fragmented governance, inequitable communication access, and unsustainable funding mechanisms. Moreover, the study reveals that the success of EWS hinges not merely on technological sophistication, but on their alignment with local contexts, community participation, and cross-sectoral coordination. Conclusion: This concludes that for EWS to be effective and equitable, they must be embedded within broader resilience strategies that emphasize localized governance, long-term capacity building, and inclusive risk communication. By reorienting EWS toward community-driven models, stakeholders can enhance flood preparedness and reduce disaster vulnerability amid escalating climate threats. Keywords: EWS, Disaster Preparedness, Flood Management, Local Context